Some Qur'anic Terminologies of Thinking and Their Positive Impacts on the Human Life - Zamakhsyari bin Hasballah Thaib (Universitas Dharmawangsa Medan, 2025)
The holy Qur’an uses near about thirty terminologies related to the human thinking. Some of them are mentioned here in this article, such as: Conceiving, perceiving, retrieving, considering, deliberating, comprehending, grasping, reasoning, contemplating, pondering and to draw some fruitful lessons. Many of these terminologies have some additional positive connotations besides denoting the different levels of thinking. Before analyzing these terminologies, it is better to know further about the Islamic concept of knowledge and introduce it as being the important object of knowledge. The aim of this research is to know the real concept of knowledge in Islam, so that it will be easier for us to analyze the terminologies of Qur'anic thinking and their positive impacts on the human life. We also use in this article some opinions of Muslim thinkers and Western scholars in the concept of knowledge using a descriptive analytical approach, which is always being useful in search of such kind of issues related to interpretation of the Qur’an and it is worth to declare that we mention some needed examples also from the verses of the Qur'an.